Buddhism : an outline of its teachings and schools - Schumann, Hans Wolfgang (Wheaton, Ill. : Theosophical Pub. House, 1974)
A systematic arrangement of material which makes this book a reliable guide through a vast field of thought. With 39 drawing and photos. Includes tabulated synopsis of the major systems of Buddhism.
I. The Buddha's life -- II. Hinayana: the Buddhism of liberation through self effort -- Councils and sources -- The teachings of the Theravada -- 1. All existence is suffering -- 2. The subject of suffering and the three marks -- 3. Excursus: objective and subjective existence -- 4. The cycle of rebirth -- 5. The doctrine of Kamma -- 6. The cause of rebirth -- 7. Conditioned origination -- 8. The nexus of conditioned origination in detail -- 9. Conditioned origination as the foundation of individual existence -- 10. The termination of suffering -- II. The eightfold way to the termination of suffering -- 12. The goal: Nibbana -- The main schools of the Hinayana -- III. Mahayana: the monistic Buddhism of liberation by other power -- Hinayana and Mahayana: contrasts and similarities -- The Sanskrit literature of the Mahayana -- The basic teachings of the Mahayana -- 1. The Buddhology -- 2. The doctrine of the three bodies -- I. Dharmakaya -- II. Sambhogakaya -- III. Nirmanakaya -- 3. The Bodhisattvas -- The Mahayanic ways to liberation and nirvana -- 1. All existence is suffering -- 2. The way of self discipline -- 3. The way of wisdom -- 4. The Bodhisattva way -- 5. The way of faith -- 6. The cultic way -- 7. The goal: nirvana -- IV. Philosophical schools of the Mahayana -- The Madhyamaka system -- 1. Thinkers and sastras -- 2. Teachings -- The yogacara system -- 1. Thinkers and sastras -- 2. Teachings -- V. The trantrayana and the Buddhism of East Asia -- VI. A cultural historical survey -- VII. Tabulated synopsis -- VIII. Literature -- 1. Abbreviations and text editions -- 2. Translations of Indian works; secondary literature.
"Published under a grant from the Kern Foundation."
Includes bibliographical references (pages 184-188).
Keywords: Buddhism -- Doctrines; Buddhism -- Doctrines -- Introductions